Sonic education in elementary school: presence and pedagogical approaches to soundscapes in music textbooks - Marín-Liébana, Pablo; Escorihuela, Guillem; Blasco-Magraner, José Salvador; Hurtado-Soler, Amparo; Botella-Nicolás, Ana María (Frontiers in Education, 2025)
IntroductionIn contemporary education, soundscapes are increasingly recognized as key elements for fostering critical listening, environmental awareness, and students' active engagement with their surroundings. Nevertheless, these topics remain largely underrepresented in educational materials, particularly at the primary level. This study investigates how soundscapes are addressed in primary school music and dance textbooks within the framework of the LOMLOE policy in Valencia, Spain.MethodsA content analysis was conducted on a sample of 18 textbooks from the three most widely used series: Musicando (Bromera), Nuevo Acordes (Santillana), and Música en Moviment (Tàndem). The analysis focused on the presence of soundscape-related content and the pedagogical approaches employed.ResultsThe analysis revealed a limited presence of soundscape topics, accompanied by a predominant reliance on traditional, activity-based pedagogical methods. Few activities promoted critical thinking or context-based auditory awareness. Furthermore, the soundscapes presented often lacked connection to students' everyday experiences, neglecting both daily and technological sounds.DiscussionThese findings suggest that current textbooks reflect a conservative conception of music education, limiting its potential as a tool for social and environmental engagement. The study highlights the need to reframe educational materials using more critical, inclusive, and contextually grounded perspectives, in order to better integrate soundscapes into primary music education.